333 WHY DO PREGNANCIES CONTINUE TO OCCUR ON ISOTRETINOIN: RESULTS OF A SURVEY STUDY. (1st January 2005) - Robertson, J.; Chambers, T.; Koren, G.; Lavigne, S.; Miller, R.; Polifka, J.; Moore, C.; Carey, J. C.
Abstract : Soon after its appearance on the market 20 years ago, isotretinoin (Accutane) became established as one of the most potent human teratogens. To prevent the occurrence of pregnancies on the medication, programs were established in the U.S. (S.M.A.R.T.) and Canada (P.P.P.). Despite these programs, pregnancies on isotretinoin continue to occur in North America. In recent years Teratology Information Services (TIS) report an increase of calls for exposure to the medication. In Utah alone, after receiving only 1 or 2 calls a year in the 1990s, the TIS recorded 13 calls in 2000 and 3-10 calls annually in 2001-2004. In order to determine the basis of failed pregnancy on isotretinoin, we developed a survey instrument for administration by TIS staff. The principal study OBJECTIVE was to identify barriers to the successful implementation of the components of the pregnancy prevention programs in North America. Clients, who called one of the collaborating TIS in 2003-2004, were recruited and consented to complete a survey by phone. 31 callers completed the survey; 19 from the U.S. and 12 from Canada. RESULTS included the following: 78% of callers indicated that they were not following the S.M.A.R.T. requirements to use two forms of birth control. 71% of women were not screened using two pregnancy tests, as recommended by S.M.A.R.T. Only 35% of U.S. pharmacists offered information about the risks of isotretinoin in pregnancy or the importance of using two forms of contraception. These results demonstrate that preventable exposures continue to occur due to noncompliance with current requirements of the S.M.A.R.T. or P.P.P. programs. The authors and OTIS are recommending increased regulatory safeguards using the S.T.E.P.S. Program for thalidomide as a template.